KELAYAKAN MEDIA PEMBELAJARAN BIOCARD PADA MATERI SISTEM PENCERNAAN KELAS VIII SMPN 14 PONTIANAK - Qurratul Aini; Kurnia Ningsih; Eko Sri Wahyuni (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
The interview results of the needs teacher and students at SMPN 14 Pontianak, the results obtained were that the human digestive system is the material with lowest average compare to other materials, students prefer learning media visual. This study aims to find out the feasibility of biocard learning media on the material of the human digestive system in grade VIII of SMPN 14 Pontianak. The method used in this research is Research and Development (R & D) with a development model by Borg and Gall with limitations up to stage 5 namely potentials and problems, data collection, product design, design validation and product revision. The instrument used in this study was the biocard learning media validation sheet. The biocard learning media was validated by 2 FKIP UNTAN lecturers and 3 science teachers at SMPN 14 Pontianak. The results of the validation analysis using Aiken's V for the aspects of format feasibility, content eligibility, language eligibility, and usability feasibility obtained an average value of 0.89 so that they were declared valid and the results of the reliability test using the Intraclass Correlation Coefficient test obtained an average value of 0,902 in excellent criteria.. From the results obtained, it can be concluded that the biocard learning media on the human digestive system material developed is suitable for use as a learning medium.